Curtain call - Holm, Jennifer L.; Holm, Matthew (Holm, Jennifer L. Babymouse. Tales from the locker, 2020)
All Babymouse wants is to be famous. When the middle school play, Carnival Chaos, is announced, Babymouse thinks it is her shot at stardom. Her dreams are dashed when she is cast as Clown #2, but she is determined to be the best Clown #2 ever. When the lead isn't able to make it on stage for the final scene, it will take all of Babymouse's skills to save the play.